Quantum dot - molecularly imprinted polymer nanomaterials for the fluorescence sensing of selected pharmaceutical and personal care products - Forbes, Patricia B.C. (University of Pretoria, 2019)
Thesis (PhD)--University of Pretoria, 2018.